Transport Analysis of Copper in Boac River Marinduque, Philippines - Logmao, Jenina; Orcilla, Lara Therese; Sun, Kelly Lois; Monjardin, Cris Edward; De Jesus, Kevin Lawrence (International Journal of Integrated Engineering, 2023)
In 1996, over 1.6 million cubic meters of mine tailings were released along Boac River, Marinduque, Philippines declaring it biologically dead.  Numerous studies found traces of heavy metals along this river, and bioaccumulation became a problem. Several heavy metals contaminating the river were reported to be ingestible by humans; one of which is Copper (Cu). With that, this study investigated Cu dispersion in the downstream area of Boac River.  This was first done by coordinating with the “Development of Health Index: Vulnerability to Extreme Environmental Events for Marinduque island.” (D-HIVE) project in collecting the water quality data, rainfall data, and digital elevation models (DEMs).  Using the Hydrologic Engineering Center’s River Analysis System (HEC-RAS) 6.2, the analyses were conducted by inputting the collected data.  The flood hazard maps showed minimal spread in high-elevation areas and distinct spread in low-lying areas.  The highest flood velocity was in the starting and middle points of the watershed, indicating these areas have the highest potential to lift Cu content and transport it into the downstream area and floodplain. The spatial variability maps showed that pH increases while Cu content decreases as water flows toward the downstream area. Overall, this study successfully determined the dispersion of Cu along Boac River.